Ethnomethodology Approach in Investment Decision Making in Islamic Capital Market: An Interaction and Social Practice of Market Participants - Muhammad Syahrul Hidayat; Supriyanto Supriyanto; Nurul Mazidah (Majapahit Journal of Islamic Finance and Management, 2023)
This study aims to investigate and analyze social interactions and social practices underlying investment decision-making in the Islamic capital market. The research focus includes an understanding of how Islamic values are reflected in the interaction of market participants, the communication practices used, and the impact of social context on investment decision-making. This research uses qualitative methods with an ethnomethodological approach through participatory observation, in-depth interviews, and document analysis. Researchers are involved in the daily activities of market participants, whether on the stock exchange, Islamic finance seminars, or investment forums. In-depth interviews were conducted with investors, brokers, and Islamic finance experts to gain a more in-depth perspective. The document analysis includes a study of Islamic finance literature, fatwas, and related documents. The results showed that social interaction and social practices of market participants have a significant role in making investment decisions in the Islamic capital market. Communication practices based on Islamic values play a key role in the decision-making process. The social and cultural context also influences investors’ perceptions and preferences towards Islamic financial instruments. These findings provide deep contextual insights into the factors influencing investment decisions in Islamic capital markets, which can be the foundation for the development of Islamic ethics-based investment strategies.